Aloha :)
a) Wähle als Ansatz:$$f(x)=ax^2+bx+c$$und setze die Punkte ein:
$$0=f(0)=a\cdot0^2+b\cdot0+c=c\quad\Rightarrow\quad c=0$$$$0=f(1)=a\cdot1^2+b\cdot1+c=a+b\quad\Rightarrow\quad b=-a$$$$3=f(2)=a\cdot2^2+b\cdot2+c=4a+2b+c=4a+2(-a)=2a\quad\Rightarrow\quad a=\frac{3}{2}$$Damit haben wir die Funktion:$$f(x)=\frac{3}{2}x^2-\frac{3}{2}x=\frac{3}{2}(x^2-x)$$
~plot~ {0|0} ; {1|0} ; {2|3} ; 3/2*(x^2-x) ; [[-2|3|-1|4]] ~plot~
b) Wähle als Ansatz:$$f(x)=ax^2+bx+c$$und setze die Punkte ein:
$$1=f(0)=a\cdot0^2+b\cdot0+c=c\quad\Rightarrow\quad c=1$$$$5=f(-1)=a(-1)^2+b(-1)+c=a-b+1\quad\Rightarrow\quad a-b=4\quad\Rightarrow\quad b=a-4$$$$5=f(-4)=a(-4)^2+b(-4)+1=16a-4b+1=16a\underbrace{\,-\,4a+16}_{=-4b}+1=12a+17$$$$\qquad\Rightarrow\quad12a=-12\quad\Rightarrow\quad a=-1$$Damit haben wir die Funktion:$$f(x)=-x^2-5x+1$$
~plot~ {0|1} ; {-1|5} ; {-4|5} ; -x^2-5x+1 ; [[-6|2|-2|8]] ~plot~